Identification of B cell marker genes based on single-cell sequencing to establish a prognostic model and identify immune infiltration in osteosarcoma - Zhang, Zhongmin; Zhang, Jin; Duan, Yuansheng; Li, Xuesong; Pan, Jie; Wang, Guowen; Shen, Bin (Frontiers in Immunology, 2022)
Abstract Background In recent decades, the treatment of osteosarcoma has been stagnant, so there is an urgent need to seek new therapeutic targets. B cells play a significant role in the anti-tumor process and are an important part of tumor immune infiltration. Methods We identified the marker genes of B cells based on the single cell sequencing results of osteosarcoma in the GEO database. The prognostic model was established by the TCGA database and verified by GEO data. We also compared the divergence in immune infiltration between the low-risk and high-risk groups according to the prognosis model. Finally, the differential genes in the low-risk and high-risk groups were enriched and analyzed. Results We obtained 261 B cell marker genes by single-cell sequencing and established a prognostic model of 4 B cell marker genes based on TCGA data. The model has good prediction performance in the TCGA and GEO data. We also found that there was a remarkable difference in immune infiltration between the low-risk and high-risk groups. The above results were also verified by enrichment analysis. Conclusion We established a prognostic model with good predictive performance and revealed that B cells play an indispensable role in the development of osteosarcoma. It provides a predictive index and a new therapeutic target for immunotherapy for clinical patients.